PENENTUAN MUTU CUKA NIRA AREN (Arenga pinnata) BERDASARKAN SNI 01-4371-1996 - . Baharuddin; . Syahidah; Nyni Yatni (PERENNIAL, 2009)
This study was aimed to determine quality of sugar palm vinegar (Arenga pinnata) based on SNI 01-4371-1996. The result was expected to provide material information about the quality of sugar palm vinegar based on SNI 01-4371-1996 and as a reference for further research. Nira of sugar palm as sample used in this research were obtained from Kappang Village, District Cenrana, Maros Regency, South Sulawesi Province. The process of making vinegar through by fermentation of the nira which has been obtained from the field. Vinegar is produced and then tested their quality based on SNI 01-4371-1996. The results showed that the variables that meet the SNI 01-4371-1996 on vinegar fermentation are the liquid form and flavour, acetic acid content, residue of alcohol, Pb and Cu metal contamination and arsenic contamination. Variables that not meet the SNI 01-4371-1996 are NaCl, the amount of dissolved solids, test of total sugar, contaminant of metals zinc (Zn) and microbial contamination. Key words: Sugar palm vinegar, Arenga pinnata, nira, SNI 01-4371-1996